2015
DOI: 10.1016/j.ijgo.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Client–pharmacy worker interactions regarding medical abortion in Zambia in 2009 and 2011

Abstract: Pharmacy workers exhibited increased awareness of misoprostol, less hostility, and a willingness to sell medical abortion drugs; however, they continued to provide inadequate information on misoprostol for medical abortion. Effective training of pharmacy employees is vital in increasing access to safe induced-abortion care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…The earliest study was published in 1991 (conducted in 1985), but most were published since 2010; 13 of those had not been included in an earlier literature review on this topic (Sneeringer, Billings, Ganatra, and Baird 2012). The studies were conducted in various locations in Latin America (Billings et al 2009;Bonnema and Dalebout 1992;de Oddone et al 1991;Lara, Garcia, Wilson, and Paz 2011;Miller et al 2005;Zamberlin 2007), sub-Saharan Africa (Adinma and Adinma 2013;Akiode et al 2010;Fetters et al 2015;Hendrickson et al 2015;Reiss et al 2017) South Asia (Huda et al 2014;Mishra et al 2016;Powell-Jackson, Acharya, Filippi, and Ronsmans 2015;Reiss et al 2015b;Tamang, Puri, Lama, and Shrestha 2015;Tamang and Tamang 2005), and South East Asia (Ngo, Park, and Nguyen 2012). In two of the locations, legal restrictions on abortion did not make exceptions to save the mother's life at the time of study (Senegal and Dominican Republic); in the majority abortion was allowed only to save the mother's life or to preserve her health (Nigeria, Mexico, Peru, Paraguay, Bangladesh, Kenya, and Argentina); and in the remaining locations abortion was available on socioeconomic grounds or on request (Zambia, India, Vietnam, and Nepal).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The earliest study was published in 1991 (conducted in 1985), but most were published since 2010; 13 of those had not been included in an earlier literature review on this topic (Sneeringer, Billings, Ganatra, and Baird 2012). The studies were conducted in various locations in Latin America (Billings et al 2009;Bonnema and Dalebout 1992;de Oddone et al 1991;Lara, Garcia, Wilson, and Paz 2011;Miller et al 2005;Zamberlin 2007), sub-Saharan Africa (Adinma and Adinma 2013;Akiode et al 2010;Fetters et al 2015;Hendrickson et al 2015;Reiss et al 2017) South Asia (Huda et al 2014;Mishra et al 2016;Powell-Jackson, Acharya, Filippi, and Ronsmans 2015;Reiss et al 2015b;Tamang, Puri, Lama, and Shrestha 2015;Tamang and Tamang 2005), and South East Asia (Ngo, Park, and Nguyen 2012). In two of the locations, legal restrictions on abortion did not make exceptions to save the mother's life at the time of study (Senegal and Dominican Republic); in the majority abortion was allowed only to save the mother's life or to preserve her health (Nigeria, Mexico, Peru, Paraguay, Bangladesh, Kenya, and Argentina); and in the remaining locations abortion was available on socioeconomic grounds or on request (Zambia, India, Vietnam, and Nepal).…”
Section: Methodsmentioning
confidence: 99%
“…One mystery client study in Kenya in 2013, however, reported higher provision levels (26 percent) (Reiss et al 2016). In a repeated mystery client survey in Zambia , a significant increase in misoprostol provision was recorded, from 51 percent in 2009 to 72 percent in 2011 (Hendrickson et al 2015). Misoprostol provision to mystery clients was common in legally restrictive settings such as Latin America (which studies were of mixed quality), ranging from 78-90 percent in Mexico (Billings et al 2009;Lara, Garcia, Wilson, and Paz 2011) to 64 percent in the Dominican Republic (Miller et al 2005) and 55 percent in Argentina (Zamberlin 2007).…”
Section: Characteristics Of Studies and Study Populationsmentioning
confidence: 98%
See 3 more Smart Citations